Characteristics of Commercial SiC and Synthetic SiC as an Aggregate in Geopolymer Composites. (March 2017) - Irfanita, R; Afifah, K N; Asrianti,; Subaer,
Abstract: This main objective of this study is to investigate the effect silicon carbide (SiC) as an aggregate on the mechanical strength and microstructure of the geopolymer composites. The geopolymers binder were produced by using alkaline activation method of metakaolin and cured at 70oC for 2 hours. In this study commercial and synthetic SiC were used as aggregate to produce composite structure. Synthetic SiC was produced from rice husk ash and coconut shell carbon calcined at 750oC for 2 hours. The addition of SiC in geopolymers paste was varied from 0.25g, 0.50g to 0.75g to form geopolymers composites. The chemical compositions and crystallinity level of SiC and the resulting composites were measured by means of Rigaku MiniFlexII X-Ray Diffraction (XRD). The microstructure of SiC and the composites were examined by using Tescan Vega3SB Scanning Electron Microscopy (SEM). The physical and mechanical properties of the samples were determined based on apparent porosity, bulk density, and three bending flexural strength measurements. The results showed that the commercial and synthetic SiC were effectively produced geopolymers composites with different microstructure, physical and mechanical strength.